Expression of Ki-67 and Its Association with Histological Type, Grade and Stage of Colorectal Carcinoma - Jahan, Sultana Israt; Md Badruddoza, Shah; Asafudullah, SM; Amin, Md Nurul (Ibrahim Cardiac Medical Journal, 2021)
Background & objective: The role Ki-67 as a prognostic marker has been studied in many cancers in many studies. However, only few studies reported the prognostic role of Ki-67 in colorectal carcinoma (CRC) with contradictory opinions. The present study was undertaken to assess the Ki-67 proliferation index (PI) in tissue sections of CRC and to investigate the relationship between the proliferative activity and histological type, grade and stage of the tumour. Methods: The present cross-sectional descriptive study was conducted in the Department of Pathology, Rajshahi Medical College, Rajshahi over a period of two years from September 2017 to August 2019. All clinically suspected cases of CRC and later confirmed by histopathology were the study population. A total 44 such cases were included in the study. Tissue sections from 44 formalin-fixed and paraffin-embedded tumor specimens were examined at the Department of Pathology of Rajshahi Medical College, Rajshahi. The cases were histologically classified, graded (WHO) and staged according to TNM and modified Dukes’ staging system. Ki-67 proliferation index was calculated immunohistochemically using the monoclonal antibody MIB-1, and were studied under light microscope. Expression of Ki-67 was calculated as a percentage of labeled nuclei per 500 cells counted in consecutive five high-power fields in the most reactive areas of the slides. The staining results were categorized into groups using a cut-off value of Ki-67 determined by ROC curve analysis. Results: In the present study the cases with high Ki-67 PI were significantly associated with high grade colorectal carcinoma (p = 0.005). TNM Stage-II and Stage-III tumours were more likely to be associated with high Ki-67 PI than those with low Ki-67 PI (p < 0.001). A significant association was observed between Ki-67 immuno-expression and modified Dukes’ staging of the tumours with Stage C being highly associated with high Ki-67 PI (p < 0.001). But histologic tumor type (mucinous and non-mucinous) was not found to be associated with Ki-67 proliferation index. Based on Receiver Operating Characteristic (ROC) curve analysis tumors with nuclear immunoreactivity ≥ 25% were considered as high proliferation index (PI) and < 25% as low PI. The Ki-67 at a cut-off value of >25% had high sensitivity (85.7%) in differentiating high grade CRC from the low-grade tumors but its specificity was moderate (67.6%) with overall diagnostic accuracy being 70.5%. Conclusion: The study concluded that cases with high Ki-67 PI are significantly associated with high grade CRC (poorly differentiated) than the cases with low grade CRC (well and moderately differentiated). TNM Stage-II & Stage-III and modified Dukes’ stage C also more often tend to be associated with high Ki-67 PI than with low Ki-67 PI. Ibrahim Card Med J 2020; 10 (1&2): 33-39